Pengaruh Lingkungan Kerja dan Motivasi terhadap Kinerja Karyawan Bagian Non Medis di Rumah Sakit Umum (RSU) Kota Tangerang Selatan - Sintia Desiana (Pusat Riset dan Inovasi Nasional, 2025)
The increasing need for health services, demands for high quality services, and intense competition among various health institutions require each institution to continue to improve and improve the quality of its services. This scientific work uses quantitative statistical research methods . Data collection was carried out in 3 (three) ways, namely observation, documentation study, and questionnaire. Researchers used the saturated sample method and obtained the number of samples to be studied was 69 respondents. This research uses several tests, namely data quality test, classical assumption test, hypothesis test, and finally the coefficient of determination test (R2). Based on the discussion of the research results, it can be concluded that the work environment and motivation have a significant effect simultaneously or together on employee performance at the South Tangerang City General Hospital (RSU) with an R Square value of 0.679 which indicates 67.9%. A comfortable and safe work environment and good employee motivation can realize employee performance as expected by the agency.